Short Communication: Preservation effect of Javanese turmeric and red ginger essential oils on coated frozen patin fillets - ROHULA UTAMI; KAWIJI KAWIJI; DANAR PRASEPTIANGGA; GODRAS JATI MANUHARA; LIA UMI KHASANAH; NENSI ANGGRAINI; FENY MARGITA LESTARI (Nusantara Bioscience, 2016)
Abstract. Utami R, Kawiji, Praseptiangga D, Manuhara GJ, Khasanah LU, Anggraini N, Lestari FM. 2016. Short Communication: Preservation effect of Javanese turmeric and red ginger essential oils on coated frozen patin fillets. Nusantara Bioscience 8: 264-267. Due to antimicrobial and antioxidant properties of essential oil, Javanese turmeric and red ginger potentially used as preservation agents on food. Cassava starch-based edible coating enriched with Javanese turmeric and red ginger essential oils were applied to maintaining of patin fillets quality during frozen storage. Fillets quality were analyzed based on microbiological (total plate count) and chemical properties (total volatile bases; thiobarbituric acid value). Different concentration of Javanese turmeric and red ginger essential oil enrichment were studied (0, 0.1, and 1% (v/v of distilled water)). Javanese turmeric and red ginger essential oils enrichment on coating solution significantly inhibited microbial proliferation, retarded protein deterioration and delayed lipid oxidation in fillet during frozen storage for four months. Increasing essential oil concentration showed on the increase in maintaining fish quality. The results indicated that Javanese turmeric and red ginger essential oil addition on cassava starch-based edible coating could maintain quality and extend the shelf life of frozen fish fillets and can be used as an alternative fish fillets preservation.